Compilation of Islamic Law Perspective on Divorce Lawsuit Against Husbands Who Disregard the Alimony with Compensation - Andri Yusuf (International Journal of Religion, Humanity and Cultural Heritage, 2025)
The obligation of a husband to provide alimony (nafaqah) to his wife is a cornerstone of Islamic family law, emphasizing the husband's role as the financial provider. This obligation persists even in cases of the husband's incapacity, unlike other forms of maintenance, and unfulfilled alimony becomes a debt that must be settled. This study explores the legal remedies available to wives when husbands neglect their alimony responsibilities, focusing on the Compilation of Islamic Law (KHI) in Indonesia. This research was conducted using the literature research method, examining literature materials related to the research problem. This study suggests that a wife can take legal action against her husband for divorce if he fails to fulfil his responsibility to provide for their family. The Compilation of Islamic Law states that both spouses have the right to seek legal redress if they neglect their duties.